Strategi Komunikasi Petugas BPJS Dalam Memberikan Informasi Layanan Kesehatan di Puskesmas Kec. Tebing Syahbandar - Annisa Zulfani Fani; Anang Anas Azhar (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Annisa Zulfani1, 1,2Program Ilmu Komunikasi, Universitas Islam Negeri Sumatera Utara annisa0102193147@uinsu.ac.id1, ABSTRACT. The community currently does not understand the procedures or requirements for obtaining access to BPJS health services at the puskesmas which is caused by several things, both from the factors of the community's lace mindset and the lack of innovation in socializing these health services. As a result, the BPJS service process that has been designed becomes hampered and not optimal. This study aims to: 1) Know how the Communication Strategy carried out by BPJS Officers in Providing Health Services at Puskemas Tebing Syahbandar, 2) Know what are the obstacles to the Communication strategy carried out by BPJS Officers in Providing Health Services at Puskemas Tebing Syahbandar. The results of this study show that in delivering health service information to the public, BPJS officers have implemented communication strategies including: 1) Determining the Purpose and Object of Receiving Information; 2) Perform persuasive techniques in providing health service information; 3) Build Educational Communication. The obstacles experienced by BPJS officers include: 1) Obstacles in the process of delivering information that occurs because patients are more dominant elderly 2) Social obstacles caused by the existence of people who are difficult to socialize. Keywords: Communication Strategy, Health Services, BPJS Officers